Qt 5 and OpenCV 4 computer vision projects : get up to speed with cross-platform Computer Vision app development by building seven practical projects /: get up to speed with cross-platform Computer Vision app development by building seven practical projects. (2019) - Qingliang, Zhuo
No abstract available